Faktor-Faktor yang Mempengaruhi Kinerja Karyawan Di Lmats Consulting - Ketut Adiyaksa Abdi Wibawa; Anak Agung Sagung Kartika Dewi (STIE Mandala Jember, 2023)
Human Resources is one of the important factors determining the success of the company. Employees have a dominant role in most operational activities such as planning, coordinating, organizing, executing and supervising work practices. The purpose of this study was to analyze the effect of employee welfare programs, work environment and workload on employee performance at LMATS CONSULTING. This research was conducted using the saturated sample method as many as 65 people who are employees at LMATS CONSULTING. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that the employee welfare program has a positive and significant effect on employee performance, the work environment has a positive and significant impact on employee performance and the workload has a negative and significant impact. The implication of this research is to provide empirical evidence that the theory used in the study refers to the attribution theory. This research can be used as a reference for all parties, both students and universities who want to conduct research with similar variables.